LEGAL CONSEQUENCES OF THE VALIDITY OF THE AUTHENTIC DEED IN THE NOTARY CONTRACT AGREEMENT BEFORE THE PARTIES IN THE ABSENCE OF A NOTARY - Prika Ayunda Lestari; Norman Adrianto; Muhamad Nur Alamsyah; Raden Handiriono (Ann Publisher, 2025)
Abstract Background. This study analyzes the legal consequences of the validity of authentic deeds in agreements (akad) made without the presence of a notary. Aims. An authentic deed has an important role as a strong evidence in proving the validity of an agreement. Result. However, the absence of a notary at the time of the contract can affect the validity and evidentiary strength of the deed. Conclusion. Using a normative juridical approach, this study shows that the making of deeds without the presence of a notary can cause legal uncertainty for the parties involved and potentially cause adverse legal consequences. Implementation. Therefore, the author suggests the need to affirm the obligation of the notary in ensuring his presence in person to ensure the certainty and legal force of the deed made.